Human cloning playing God or scientific progress? - Lester, Lane P.; Hefley, James C. (Grand Rapids, MI Fleming H. Revell, 1998)
Includes bibliographical references.
"Some chapters are taken largely from Cloning : miracle or menace, published in 1980 by Tyndale House"
Keywords: Human cloning -- moral and ethical aspects